Sterben: Dimensionen eines anthropologischen Grundphänomens - Borasio, Gian Domenico; Bormann, Franz-Josef (De Gruyter, 2012)
As a result of its almost total displacement from the everyday life environment death threatens to become a target for the projection of various fears. This volume takes an interdisciplinary look at this complex phenomenon, and attempts to examine its various dimensions. The presentation of the possibilities of current palliative medicine and ethical reflection upon it are shown to be of particular importance. Franz-Josef Bormann, Eberhard Karls Universität Tübingen; Gian-Domenico Borasio, Universität München.